2021
DOI: 10.1111/ijfs.15396
|View full text |Cite
|
Sign up to set email alerts
|

Improving moisture barrier and functional properties of active film from genipin‐crosslinked chitosan/astaxanthin film by heat curing

Abstract: This research aimed to improve moisture barrier and functional properties of genipin-crosslinked chitosan/astaxanthin film by heat curing. The effect of heat curing (25, 80 and 105 °C) on film properties was investigated by measuring water vapour permeability (WVP), contact angle, tensile strength (TS), elongation at break (EAB), Young's modulus (YM), opacity, chemical structure and antioxidant activity. Results showed that genipin-crosslinked chitosan/astaxanthin film and heat cured at 105 °C (CAG-105) have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…A similar trend was observed for the CS1.5G-105 film with curing at 105 °C, producing the lowest WVP value of 0.81 ± 0.01×10 -4 g mm/h/mm 2 /Pa compared with that of CS1.5G-25. These results agreed well with those obtained by Inthamat et al (2021b) and Rivero et al (2011) who reported that the molecular alterations in film structure due to curing at high temperatures, probably because the carboxylic acid could react with the amine group to form an amide resulting in water being eliminated (de Castro et al, 2013).…”
Section: Water Vapor Permeability Of Thermal Curing Filmssupporting
confidence: 92%
See 1 more Smart Citation
“…A similar trend was observed for the CS1.5G-105 film with curing at 105 °C, producing the lowest WVP value of 0.81 ± 0.01×10 -4 g mm/h/mm 2 /Pa compared with that of CS1.5G-25. These results agreed well with those obtained by Inthamat et al (2021b) and Rivero et al (2011) who reported that the molecular alterations in film structure due to curing at high temperatures, probably because the carboxylic acid could react with the amine group to form an amide resulting in water being eliminated (de Castro et al, 2013).…”
Section: Water Vapor Permeability Of Thermal Curing Filmssupporting
confidence: 92%
“…Similarly, these peaks were moved to 1728 cm -1 and 1577 cm -1 for CS1.5G-105. A peak at 1410 cm -1 of CS1.5G-80 and CS1.5G-105 was detected when those films had higher density due to heat curing, probably attributed to the C-C binding between the genipin molecules already linked to the amino groups of the chitosan chain (Inthamat et al, 2021b).…”
Section: Effect Of Thermal Curing On Chitosan and Crosslinked Chitosa...mentioning
confidence: 99%
“…The polyene chain of AST is capable of a strong antioxidant effect with a unique chemical structure that traps radicals [ 55 ], in which the long-conjugated double-bonded polyene possesses ROS removal capability by regulating the redox balance due to its inherent lipophilic and hydrophilic properties. Moreover, it exhibits higher antioxidant activity than other carotenoids such as β-carotene and lutein because of the presence of two oxygen groups, including hydroxyl (OH) and carbonyl (C = O) in each of the rings [ 56 ]. Consequently, as can be seen from the ABTS and DPPH assay of GO and AST, the synergistic combination of the AST and GO may provide unprecedented scenarios as new antioxidant material to those working in this nanobiotechnology field, thereby these materials can be considered as a strong candidate for an antioxidant platform for the treatment of various oxidative stress-mediated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…112 Interestingly, Inthamat et al (2021) improved the moisture barrier of a film based on chitosan and astaxanthin by heat curing. 113 Furthermore, brittleness and rigidity are common issues faced by bioplastics, which may be overcome with mechanical reinforcements. 1 For example, modified silica nanoparticles improved the mechanical and barrier properties of a chitosan film.…”
Section: Packaging Properties For Commercialisationmentioning
confidence: 99%